(untitled) (Journal of the College of Basic Education, 2025)
The aim of the research is to identify the effectiveness of using the doll as a teaching and educational tool in developing artistic expression among primary school students. In her research procedures, the researcher relied on the experimental design (experimental and control group). The two research groups were conducted in a simple random way, with (20) students in each group, so that the total number of the research sample was (40) students. The procedures of the current research required the preparation of study plans according to the use of the puppet as a teaching and educational tool to teach the two research groups (experimental and control), in addition to that, the researcher prepared a form for observing the skillful performance of artistic expression in drawing, using the researcher’s statistical bag (Spss) to process her research data.